Temperature Dependence of Laminar Burning Velocity in Ammonia/Dimethyl Ether-air Premixed Flames - Cai, Tao; Zhao, Dan (Journal of thermal science, 2022)
The combustion of ammonia (NH 3 ) has attracted wide interest in fuel vehicle engines, marine engines, and power generators to mitigate carbon dioxide emissions. Unfortunately, the relatively low laminar flame speed presents a technical barrier for this renewable fuel to be used in practice. This work is concerned with numerical examining the effects of elevating inlet temperature on the laminar burning velocity of NH 3 /air flames with various contents of dimethyl ether (DME) using 1D freely propagating flame calculations, and to shed light on the flame enhancement mechanism. For this, the mechanism is first validated by comparing the numerical predictions with experimental data. Results show that increasing the inlet temperature has a positive effect on the laminar burning velocity of pure NH 3 /DME/air flames. It is revealed that elevating inlet temperature contributes to a higher adiabatic flame temperature, which is beneficial to the overall chemical reaction rate. Furthermore, the thermal diffusivity of the binary mixture is observed to increase substantially as well. Further kinetic and sensitivities analyses reveal that the inlet temperature has a minimal effect on the reaction pathway, leading to the relative importance of the dominant chain branching over terminating reaction steps to be varied negligibly. The present work confirms that the flame speed enhancement with increasing inlet temperature is primarily the synergetic result of the thermal and diffusion effects, rather than the chemical effect.